The Transformative Power of Challenge-Based Learning in Cultivating 21st-Century Skills - Nawawi, Sulton; Johari, Asni; Siburian, Jodion; Anggereini, Evita (Universitas Pendidikan Ganesha, 2024)
This research addresses the implementation of effective learning models for developing 21st-century skills, particularly critical and creative thinking abilities. Furthermore, there remains insufficient understanding of how the Challenge-Based Learning (CBL) model contributes to enhancing higher-order thinking skills across diverse educational contexts. This study aims to analyze the impact of implementing the CBL model on fostering critical thinking, creative thinking, and collaborative skills among students. Using a systematic literature review with a descriptive qualitative design, the research examined 33 scientific articles sourced from the Scopus, Google Scholar, and SINTA databases, published between 2010 and 2024. Data collection was conducted with the assistance of the Publish or Perish application and VOSviewer to visualize and analyze data networks. Thematic analysis techniques were employed to identify trends and patterns in the application of the CBL model. The findings indicate that the CBL model effectively enhances higher-order thinking skills, learner engagement, collaboration, and creativity. However, challenges such as limited resources and insufficient institutional support were also identified. In conclusion, while the CBL model significantly promotes the development of critical and creative thinking skills, addressing institutional and resource constraints is essential for maximizing its impact in educational settings.